miR-1301-3p Promotes Cell Proliferation and Facilitates Cell Cycle Progression via Targeting SIRT1 in Gastric Cancer - Luo, Dakui; Fan, Hao; Ma, Xiang; Yang, Chao; He, Yu; Ge, Yugang; Jiang, Mingkun; Xu, Zekuan; Yang, Li (Frontiers in Oncology, 2021)
So far, many existing evidences indicate that microRNAs (miRNA) are closely associated with the tumorigenesis and progression of various tumors. It has been reported that miR-1301-3p is abnormally expressed in several malignant tumors. However, the role of miR-1301-3p in gastric cancer (GC) remains unclear and is worth studying. Through qRT-PCR, the expression of miR-1301-3p and SIRT1 were detected in GC tissues and cells. The cell proliferation and cell cycle were measured through CCK-8 assay and clone formation assay. Dual luciferase reporter assay was used to determine the target of miR-1301-3p. Though tumorigenesis assay, we monitored the effect of miR-1301-3p on GC cell growth in vivo. miR-1301-3p was upregulated in GC tissues and cells in our study. Overexpression of miR-1301-3p accelerated GC cell proliferation, cell cycle progression and tumorigenesis. Notably, altering the expression miR-1301-3p caused deregulation of Cyclin D1, CDK4, c-Myc and P21. Furthermore, SIRT1 was the direct target of miR-1301-3p by luciferase reporter assay. After transfecting with miR-1301-3p inhibitor, we found that knockdown of SIRT1 could enhance the ability of proliferation. Our results identify miR-1301-3p as a novel potential therapeutic target that is associated with the tumorigenesis and progression of gastric cancer.